INTERPERSONAL MEANING IN ZAKIR NAIK’S ISLAMIC SPEECH - Diana Sopha; Yayuk Yuliana; Cita Ayni Putri Silalahi; Mayasari Mayasari; Bobby Chaniago; Farah Syakila; Siti Aisyah (Fakultas Sastra UMN AL Washliyah, 2026)
This research explores how interpersonal meaning is constructed in the Islamic speeches of Zakir Naik by applying the framework of Systemic Functional Linguistics (SFL). Within the context of ‘dakwah’, language operates not only as a channel for delivering religious knowledge but also as an interactive resource through which speakers establish authority, express conviction, and engage their audiences. As an internationally recognized Islamic preacher, Zakir Naik employs distinctive linguistic strategies that warrant systematic linguistic investigation. This research adopts a qualitative descriptive approach and examines selected transcripts of Zakir Naik’s public speeches. Analysis is conducted using the interpersonal metafunction of SFL, focusing specifically on the grammatical systems of mood. The clause is treated as the main unit of analysis, as it represents the primary locus of interpersonal meaning. Each clause is categorized based on its mood type. The result is declarative clauses are predominantly used, indicating a strong tendency toward asserting information and reinforcing religious authority.